카훗(Kahoot!) 앱을 활용한 초등영어 이야기기반 읽기, 쓰기 수업: 문항 제작 활동 및 오류 수정 양상을 중심으로 - 신승희; Shin Seunghee; 김태은; Kim Tae-eun (Multimedia-Assisted Language Learning, 2020)
English education in Korea is actively utilizing classes that combine various techniques and platforms, away from textbook-oriented classes. In line with these changes, Kahoot! which is an educational game-based application has started being used in classes. Kahoot! has a special function that leads students to create question items on their own, and the process of making question items allows them to actively promote interaction and cooperation. Moreover, Kahoot! application is suitable to enhance understanding of the story. With the use of Kahoot! and stories for teaching English reading and writing in the elementary English class, the purpose of the study is to analyze the nature of question items students created by using Kahoot! and also investigate their pre- and post-writing in order to find out whether experience of solving question items influences error correction in their writing. The participants of the study were twenty fourth-grade students in an elementary school. The findings of the study revealed that students are more likely to immerse themselves in learning settings while they actively create question items. Seven types of question items were found, which encompass items questioning about content of a story, meaning of words or phrases, spelling, background knowledge, author, illustration, and fun. In addition, using Kahoot! application made improvements in appreciation of a story and writing skills among students. The study has significance in that it confirmed Kahoot! application can be an effective tool for elementary English reading and writing classes.